2016
DOI: 10.1093/gji/ggw365
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of extreme swell events on La Réunion Island from microseismic noise

Abstract: S U M M A R YOcean wave activity excites seismic waves that propagate through the solid earth, known as microseisms, which, once recorded on oceanic islands, can be used to analyse the swell. Here, we analyse the microseismic noise recorded in different period ranges by the permanent seismic station RER on La Réunion Island and by a temporary network of 10 broad-band seismic stations deployed on the island to analyse extreme swell events. We perform a comparative analysis of cyclonic and austral swell events b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…In the 2F microseism band (3-10 s), normally attributed to the interaction of broadly directional waves directly from typhoons, Davy et al (2016) found lower frequency microseisms (7-10 s) attributed to the interaction of a swell with its own coastal reflection (compare with results of Chi et al, 2010, in prior paragraph). In one instance (during Tropical Cyclone Dumille in January 2013), Davy et al (2016) describe the interaction between waves from the nearby Tropical Cyclone Dumille, with waves generated by a distant extra-tropical storm in the Southern Indian ocean. Duennebier et al (2012) suggested that the "background" microseismic level at frequencies below 0.4 Hz at Station ALOHA is (1) uncorrelated to local wind speeds and (2) attributed to the double-frequency microseisms due to incident long period swells interacting with their nearby coastal reflection.…”
Section: Journal Of Geophysical Research: Solid Earthsupporting
confidence: 66%
See 2 more Smart Citations
“…In the 2F microseism band (3-10 s), normally attributed to the interaction of broadly directional waves directly from typhoons, Davy et al (2016) found lower frequency microseisms (7-10 s) attributed to the interaction of a swell with its own coastal reflection (compare with results of Chi et al, 2010, in prior paragraph). In one instance (during Tropical Cyclone Dumille in January 2013), Davy et al (2016) describe the interaction between waves from the nearby Tropical Cyclone Dumille, with waves generated by a distant extra-tropical storm in the Southern Indian ocean. Duennebier et al (2012) suggested that the "background" microseismic level at frequencies below 0.4 Hz at Station ALOHA is (1) uncorrelated to local wind speeds and (2) attributed to the double-frequency microseisms due to incident long period swells interacting with their nearby coastal reflection.…”
Section: Journal Of Geophysical Research: Solid Earthsupporting
confidence: 66%
“…Davy et al () and Davy et al () show observations of microseisms and ocean swell generated by tropical cyclones around Reunion Island in the Indian Ocean. In the 2F microseism band (3–10 s), normally attributed to the interaction of broadly directional waves directly from typhoons, Davy et al () found lower frequency microseisms (7–10 s) attributed to the interaction of a swell with its own coastal reflection (compare with results of Chi et al, , in prior paragraph). In one instance (during Tropical Cyclone Dumille in January 2013), Davy et al () describe the interaction between waves from the nearby Tropical Cyclone Dumille, with waves generated by a distant extra‐tropical storm in the Southern Indian ocean.…”
Section: Discussion Of Results In the Context Of Prior Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the oceanic waves also propagate to the north, behind the cyclone, the southern side of La Réunion is impacted by the swell several hours after the passage of the cyclone (Figure f). Analyzing the microseismic noise using permanent and nonpermanent seismic stations, Davy et al () showed that microseismic noise was still giving a recordable signal when Bejisa was located south of the island confirming the presence of northward swell after the passage of the TC.…”
Section: Description Of the Fully Coupled Owa Simulationmentioning
confidence: 99%
“…We observe that the secondary microseism noise level is minimum during local summer, with higher levels occurring during local winter when the Southern Ocean experiences violent winter storms. The relatively higher secondary microseisms in austral winter could also be explained by instances of icebreakups and near-coastal interactions related to iceberg reflections (Grob et al 2011;Davy et al 2016;Pratt et al 2017;Lepore & Grad 2018). For the primary microseism band, noise levels are reduced in the austral winter.…”
Section: Seasonal Variations Of Microseismic Signalmentioning
confidence: 99%